Food metaphors and utopias of the sugar 'sertao': historical, cultural and socio-environmental factors - Alves Marques, Francisco Claudio [UNESP]; Marques Porto, Teresa Augusta [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2019)
In this article we intend to point out some of the historical, cultural and socioenvironmental factors responsible for the construction of current food metaphors and utopias in the popular literature of the Brazilian Northeast. More specifically, this article focuses in the Zona da Mata since this was the region that thrived most under the Colony, mainly due its strong European and African cultrural legacies.
Keywords: Food metaphors; Utopias; Allegories; Popular literature